Nursing Care and Clinical Considerations in the Management of Suction Drains - kaabi, Sarah Hussain; Shaykhah Rasheed Binmozan; Faten Abdulelah Saad; Maryam Musayeb Assab Al-inaz; Tahani Mudhhi Awadh Alanazi; Noha Mohammad Baiedi; Reem mohammed hadi ameri; Alanood Mawakh Alotaibi; Hani abdullah alawad; Jawaher Aiyedh Almutairi; et al. (Saudi Journal of Medicine and Public Health, 2025)
Background: Suction drains are widely used in postoperative care to prevent fluid accumulation, support wound healing, and allow early detection of complications. However, their routine use remains controversial due to associated risks and inconsistent evidence of benefit. Aim: This article aims to review the nursing care and clinical considerations involved in the management of suction drains, emphasizing indications, contraindications, techniques, and multidisciplinary roles. Methods: A narrative review approach was used, synthesizing current clinical evidence and nursing practice guidelines related to suction drain use, management, and complications. Results: Suction drains were shown to be effective when used selectively based on surgical and patient-related factors. Proper insertion technique, vigilant monitoring, accurate documentation, and early removal significantly reduced complications such as infection, blockage, and fistula formation. Nursing care was identified as central to safe drain management. Conclusion: Selective use and meticulous nursing management optimize patient outcomes and minimize drain-related risks.